Designing biologic selectivity for inflammatory bowel disease – role of vedolizumab - Krupka N; Baumgart DC (Dove Medical Press, 2014)
Niklas Krupka, Daniel C Baumgart Division of Gastroenterology and Hepatology, Department of Medicine, Charité Medical School, Humboldt-University of Berlin, Berlin, Germany Abstract: Crohn’s disease and ulcerative colitis are two chronic inflammatory bowel conditions. Current approved biologic therapies are limited to blocking tumor necrosis factor alpha. Unfortunately, some patients are primary nonresponders, experiencing a loss of response, intolerance, or side effects. This defines an unmet need for novel therapeutic strategies. The rapid recruitment and inappropriate retention of leukocytes is a hallmark of chronic inflammation and a potentially promising therapeutic target. Here we discuss the clinical trial results of vedolizumab (anti-α4β7, LDP-02, MLN-02, and MLN0002) and its impact on future management of inflammatory bowel disease. Keywords: ulcerative colitis, Crohn’s disease, vedolizumab, MLN0002, MLN-02, LDP-02, anti-α4β7